Possibilities of the eKhNUIR use of statistical methodology are in educational process - Kushchenko, О.I.; Кущенко, Е.И.; Кущенко, О.І. (Kharkiv, 2019)
POSSIBILITIES OF ELECTRONIC KHARKIV NATIONAL UNIVERSITY INSTITUTIONAL REPOSITORY THE USES OF STATISTICAL METHODOLOGY IN EDUCATIONAL PROCESS. The article reveals the fundamental principles and essence of market statistics tourism product. It considers detailed the system of basic indicators as a methodology of statistical evaluation and analysis of tourist activities, as well as its competitiveness at different levels. In this case, statistical evaluation covers international and domestic tourism. International tourism development indicators are important to develop strategies and tactics of the tourism product of the country. Intelligently chosen to analyze the statistical methods are always successful. All given indicators make the foundation of the knowledge base needed to make management decisions in the field of tourism industry.
Можливості eKhNUIR використання статистичної методології у навчальному процесі
Возможности eKhNUIR использования статистической методологии в учебном процессе
Kushchenko О.I., Candidate of economic sciences, Ph.D., Associate Professor of statistics, accounting and auditing. Kharkiv V.N. Karazin National University.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Business and economics; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; Research Subject Categories::SOCIAL SCIENCES::Statistics, computer and systems science::Statistics; Quantity; value of a particular quantity; absolute and relative quantities; power average and structural quantities; system of statistical indicators; variation analysis; index analysis; dynamic sequences; seasonal fluctuations in tourism; eKhNUIR